2013
DOI: 10.1530/rep-13-0239
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of docosahexaenoic acid on preterm and term placental pro-oxidant/antioxidant balance

Abstract: Docosahexaenoic acid (DHA) supplementation in pregnancy may confer some clinical benefits; however, this compound can exert pro-oxidant effects. In this study, we investigated the effects of DHA on pro-oxidant/antioxidant balance in term and preterm placental explants, assessing oxidative stress marker concentrations, antioxidant capacity and pro-inflammatory cytokine production. Term (nZ8) and preterm (nZ9) placental explants were exposed to lipopolysaccharide (LPS, 1 ng/ml), DHA (1, 10 and 100 mM), and DHA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…These findings are consistent with an in vitro study, in which treatment of placental BeWo cells with modest levels of DHA reduced oxidative DNA damage and increased cell survival when challenged by an oxidative insult (Shoji et al 2009). Similarly, in human placental explants, DHA administration reduced LPS-induced oxidative damage and restored antioxidant capacity (Stark et al 2013). Dietary n-3 PUFAs may also reduce ROS generation, given that they increase Ucp2 mRNA expression in mouse white adipose tissue (Hun et al 1999) R148 M L Jones and others placental tissue, being predominantly expressed by the syncytiotrophoblast (Stark et al 2012), although maternal dietary n-3 PUFA supplementation in the rat did not affect placental Ucp2 mRNA expression in our recent study (Jones et al 2013c).…”
Section: Omega-3 Fatty Acids and Placental Oxidative Stresssupporting
confidence: 87%
See 2 more Smart Citations
“…These findings are consistent with an in vitro study, in which treatment of placental BeWo cells with modest levels of DHA reduced oxidative DNA damage and increased cell survival when challenged by an oxidative insult (Shoji et al 2009). Similarly, in human placental explants, DHA administration reduced LPS-induced oxidative damage and restored antioxidant capacity (Stark et al 2013). Dietary n-3 PUFAs may also reduce ROS generation, given that they increase Ucp2 mRNA expression in mouse white adipose tissue (Hun et al 1999) R148 M L Jones and others placental tissue, being predominantly expressed by the syncytiotrophoblast (Stark et al 2012), although maternal dietary n-3 PUFA supplementation in the rat did not affect placental Ucp2 mRNA expression in our recent study (Jones et al 2013c).…”
Section: Omega-3 Fatty Acids and Placental Oxidative Stresssupporting
confidence: 87%
“…An in vitro study on placental cells by Shoji et al (2009) demonstrated enhanced lipid peroxidation and reduced cell survival in response to high levels of DHA administration (100 mM), although modest levels (1 or 10 mM) reduced DNA oxidative damage and enhanced cell survival rate. This was recently supported by Stark et al (2013), who found high doses of DHA administration (100 mM) in term placental explants enhanced lipid peroxidation and DNA oxidative damage, while more modest doses (1 or 10 mM) reduced LPS-induced oxidative damage and restored antioxidant capacity. Our in vivo research has found that despite relatively high dietary n-3 PUFA supplementation in pregnant rats, placental levels of the ROS-induced lipid peroxidation marker, F 2 -isoprostanes, were reduced ( Fig.…”
Section: Potential Risks Of Omega-3 Dietary Supplementationmentioning
confidence: 70%
See 1 more Smart Citation
“…The oxidative stress in the placenta has extensively been linked with unsaturated fatty acids. Studies on placental BeWo cell lines, explants, and rats indicate that at lower doses, omega 3 fatty acid (especially DHA) reduces placental oxidative stress and oxidative DNA damage and increases the levels of resolvins, protectins, and total antioxidant capacity . However, in contrast, free radicals are also known to peroxidize LCPUFA, which is injurious to the cells .…”
Section: Regional Development and Function Of The Placenta: Possible mentioning
confidence: 99%
“…They are likely to be complex as DHA not only has the potential to be beneficial, but also fish oil supplementation has been reported to promote cytokine production and oxidative stress in mice. In addition, the balance of the potential beneficial and adverse effects of DHA appear to vary with the gestational age of the placenta .…”
mentioning
confidence: 99%